Automatic Detection Of Seizure Activity From EEG Recordings Of Genetic Rat Model Of Absence Epilepsy - Ozmen, Besir; Yavuz, Melis; Carcak, Nihan; Oglu, Medine Gulcebi Idriz; Molnar, Zoltan; Onat, Filiz; Ciftci, Rifat Koray (IEEE, 2021)
29th IEEE Conference on Signal Processing and Communications Applications (SIU), ELECTR NETWORK, JUN 09-11, 2021
Keywords: Spike\\-wave discharge; EEG; Epilepsy; GAERS